Small-group collaboration and individual knowledge acquisition: The processes of growth during adolescence and early adulthood. (April 2019) - Howe, Christine; Zachariou, Antonia
Abstract: Research into small-group collaboration during middle to late childhood shows that while individual understanding can be promoted through exchanging differing opinions, the joint analyses that groups construct while collaborating play a tangential role. Individuals may or may not accept these constructions depending upon processes of reflection and reconciliation that are triggered through difference and sometimes occur post-group. Recognizing a dearth of research with older participants (together with inconclusive suggestions that collaborative constructions may become more significant with age), the reported study examines the impact of small-group collaboration during adolescence and early adulthood. Forty-six pairs of students aged between 10 and 22 years worked on a computer-presented task that required them to discuss and predict the trajectories objects follow when they fall from stationary or moving carriers. Associations between group dialogue and post-test performance confirmed a key role for differing opinions while collaborative constructions turned out to have little relevance. Highlights: Extensive data on adolescents' and young adults' understanding of object fall. Dialogue around differing opinions shown to boost understanding. Knowledge growth found to be unrelated to the quality of group analyses. Growth interpreted as the interplay of dialogue, meta-cognition, and feedback. Processes that apply with older learners parallel those established with children.